A global database of composite volcano morphometry - Grosse, Pablo (2014)
We present a global database on the subaerial morphometry of composite volcanoes. Data was extracted from the 90 m resolution Shuttle Radar Topography Mission (SRTM) digital elevation model (DEM). The 759 volcanoes included in the database are the composite (i.e. polygenetic) volcanoes listed in the Smithsonian Institution Global Volcanism Program (GVP) database that are covered by the SRTM DEM, have a constructional topography and a basal width larger than 2 km. The extent of each volcano edifice was defined using the NETVOLC algorithm, which computes outlines by minimizing a cost function based on breaks in slope around the edifices. Morphometric parameters were then calculated using the MORVOLC algorithm. The parameters characterize and quantify volcano size (basal width, summit width, height, volume), profile shape (height/basal width and summit width/basal width ratios), plan shape (ellipticity and irregularity indexes) and slopes. In addition, 104 well defined and relatively large summit craters/calderas were manually delineated and specific parameters were computed. Most parameters show large variation without clear separations, indicating a continuum of volcano morphologies. Large overlap between the main GVP morphologic types highlights the need for a more rigorous quantitative classification of volcano morphology. The database will be maintained and updated through a website under construction.